The Gale encyclopedia of cancer a guide to cancer and its treatments - Longe, Jacqueline L. (Gale virtual reference library, 2006)
Comprehensive survey of 120 cancers, cancer drugs, traditional and alternative treatments, side effects and diagnostic procedures.